Seasonal climate impact on Brazilian pasture (Brachiaria brizantha cv Marandu): growth rate, CO2 efflux, and irrigation strategies - Pereira-Flores, Milton E.; Justino, Flavio; Rodrigues, Jackson M.; Boehringer, Davi; Melo, Anderson Adriano Martins; Cursi, Andressa G.; da Costa Pereira, Vagna; Pereira, Odilon Gomes; Ruiz-Vera, Ursula M. (Theoretical and applied climatology, 2023)
This study explores the soil carbon efflux and pasture growth during summer-fall and winter-spring in two different years based on field and lysimeter experiments. Soil respiration, soil and air temperatures, leaf photosynthesis, plant dry weight, and leaf area index are quantified to characterize the influence of seasonality in the Brachiaria growth, production, and efflux. It is found that the transient variation of CO 2 efflux was highly correlated with rainfall ( r = 0.87, p < 0.05), but least correlated with soil temperatures ( r = 0.5, p < 0.05). The CO 2 efflux and plant response to different levels of reposition of evapotranspiration (irrigation) demonstrated that irrigation during the dry season reduces growth of Brachiaria in response to lower soil moisture and low temperatures. It is found that lower temperatures are a limiting factor when the soil moisture is below 32% of the field capacity. Moreover, it has been observed that soil moisture by around 50% is a key practice for mitigating the effect of seasonality. Insofar as CO 2 efflux is concerned, it is found that even at low and moderate temperatures, precipitation leads to changes in soil CO 2 efflux due to the amount of soil moisture.